THE EFFECT OF LEARNING DISCIPLINE AND LEARNING ENVIRONMENT ON STUDENTS' LEARNING OUTCOMES AT SMP NEGERI 1 DIMEMBE - Listriyanti Palangda; Gilly Marlya Tiwow; Arya Mario Ngangi (Program Studi Pendidikan Bahasa Inggris, 2025)
The main problem in this study is the low social studies learning outcomes which are thought to be influenced by the lack of learning discipline and a less supportive learning environment. This study aims to determine the effect of learning discipline and learning environment on the learning outcomes of Social Studies (IPS) of class VIII students of SMP Negeri 1 Dimembe. This study uses a quantitative approach with a survey method. The sample in this study amounted to 54 students selected through purposive sampling techniques. The instruments used were questionnaires to measure the level of learning discipline and learning environment, as well as documentation values ​​to determine students' social studies learning outcomes. Data analysis was carried out using multiple linear regression. The results of the study showed that learning discipline had a positive and significant effect on students' social studies learning outcomes. Likewise, the learning environment had a positive and significant effect on social studies learning outcomes. Simultaneously, learning discipline and learning environment had a significant effect on social studies learning outcomes with a fairly strong contribution. These findings indicate that improving student learning outcomes does not only depend on academic ability, but also on non-cognitive factors such as learning habits and a supportive environment. Therefore, efforts to improve social studies learning outcomes need to include strengthening student discipline and improving the learning environment, both at school and at home.